Prevalence and Predictors of COPD in Indonesian Smokers Attending Posbindu Community Health Centers: A Cross-Sectional Analysis - Dian Mutia Sari; Besral Besral; Ratna Djuwita; Triya Damayanti; Farida Murtiani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a major global health burden, particularly in low- and middle-income countries. In Indonesia, the high prevalence of smoking, coupled with underdiagnosis and limited healthcare access, contributes substantially to COPD cases. Identifying key risk factors is critical to strengthen prevention and management strategies. This study aimed to determine the prevalence of COPD among smokers attending POSBINDU community health center in Indonesia and to identify significant predictors associated with the disease. Methods: A population-based cross-sectional study was conducted in March 2023 across Integrated Care Posts (Posbindu) in Yogyakarta and East Java. A total of 548 smokers aged ?40 years were recruited using convenience sampling, which may limit generalizability. Only 17 COPD cases were identified (3.1% prevalence), constraining statistical power for multivariate analyses. Data collection involved structured questionnaires and spirometry testing following American Thoracic Society guidelines. Descriptive statistics, bivariate analysis, and multivariate logistic regression were used to identify independent predictors of COPD. Results: The prevalence of COPD was 3.1% (17/548). Most participants were male (98.2%) and aged 40-49 years (44.2%). Bivariate analysis showed significant associations between COPD and sputum production (OR = 4.79; P = 0.001), shortness of breath (OR = 3.11; P = 0.017), asthma (OR = 23.03; P <0.001), cardiovascular disease (OR = 11.67; P = 0.005), and abnormal spirometry (OR = 12.59; P <0.001). In multivariate analysis, sputum production (AOR = 3.99; P = 0.019) and asthma (AOR = 8.64; P = 0.020) remained strong independent predictors. Conversely, a Brinkman Index ?20 pack-years showed a paradoxical protective effect (AOR = 0.16; P = 0.023). Conclusion: This study highlights the importance of early screening and intervention among high-risk smoker populations. Community-based platforms such as Posbindu can play a critical role in facilitating prevention, early diagnosis, and improved management of COPD.